Beyond the post-political: Exploring the relational and situated dynamics of consensus and conflict in planning. (August 2019) - Legacy, Crystal; Metzger, Jonathan; Steele, Wendy; Gualini, Enrico
This Special Issue explores the problematique of the consensus and conflict binary that has emerged in the critical analysis of the post-political urban condition. Focusing on the interstitial spaces existing between consensus and conflict reveals a more relational dynamic that positions consensus and conflict as co-constitutive and continuously being shaped by the performance of politics by state and non-state actors. Critiques of the post-political tend to fail to engage with the conditions that lead to citizen actors acting in political ways beyond the formal processes of planning and decision-making, or when consensus or conflict is used by oppressive politics to produce exclusion and reproduce inequality. In addition to introducing the five papers appearing in this special issue, in this opening editorial, we argue the need to cast attention towards the new expressions of political participation generated by different citizen actors. Critically engaging with these varied expressions may reveal new ways of conceptualising participation that can create new informal spaces where injustices and inequalities are voiced and the structures and hegemonies created are exposed.